PROMOTING HUMAN RIGHTS LITERACY AMONG SCHOOL CHILDREN THROUGH DESIGN EDUCATION - Kuo-Kuang Fan; Chang, Chia-Lin (Journal of Dharma, 2021)
This study critically and creatively explores ways to promote the cognition and design skills of elementary school students on human rights through the process of design education and to cultivate their attitude towards sustainable development that values human dignity. In the curriculum process, the researcher guided the students to select several human rights problems that could often be found in the community and propose design solutions to these problems through brainstorming, discussion, practice, and correction. Through the induction of observation focus, group interviews, design work analysis, and other methods, we could understand the students’ learning performance and experience. A critical analysis of the data shows students’ change and improvement of human rights literacy in this learning process. The study found that students’ active participation in the design practice of human rights could effectively construct their concept and identity of human dignity, which made the network system of learning concepts more complete and concrete, promoting the possibility of sustainable development.